MEMBERSHIP IN NATIONAL HEALTH INSURANCE AMONG WORKERS IN INDONESIA - Wulandari, Ratna Dwi; Laksono, Agung Dwi; Tumaji, Tumaji; Herawati, Maria Holly; Pracoyo, Noer Endah; Kusrini, Ina (Universitas Airlangga, 2024)
Background: The government regulates National Health Insurance (NHI), making it mandatory for everyone. However, at this time, only some, including workers, are NHI members. Moreover, the government regulates who pays these workers' premiums. Aims: The study aimed to analyze the disparities of occupation type in NHI membership among workers in Indonesia. Methods: We involved 22,275 workers in the analysis. The analyzed variables included NHI's membership, occupation type, residence type, age group, gender, education level, marital status, and wealth status. The study employed binary logistic regression in the final step. Results: The results showed that government employees were 11.864 times more likely to be a member of NHI than the informal sector (95%CI 11.811-11.917). The private sector was 1.646 times more likely than the informal sector to be an NHI member (95%CI 1.643-1.648). Meanwhile, entrepreneurs were 0.828 times less likely to be NHI members than the informal sector (95%CI 0.827-0.829). The study found six control variables related to NHI membership: residence, age, gender, education, marital, and wealth status. Conclusion: The study concluded that NHI membership disparities existed based on occupation type. Accordingly, government employees, the private sector, the informal sector, and entrepreneurs are the most likely to become NHI members. Keywords: health insurance, health policy, national health insurance, occupation type.